Lumber Volume and Value Recovery from Small-Diameter Black Cherry, Sugar Maple, and Red Oak Logs - Jan Wiedenbeck; Matthew S. Scholl; Paul R. Blankenhorn; Charles D. Ray (BioResources, 2016)
While only a very small percentage of hardwood logs sawn by conventional sawmills in the U.S. have small-end diameters less than 10 in, portable and scragg mills often saw smaller logs. With the closure of regionally important oriented strand board and pulpwood operations, small-diameter logs are considered to have no value in some markets. This study was conducted to assess the volume and value of lumber produced from small-diameter hardwood logs of three important commercial species: red oak, sugar maple, and black cherry. Value assessments included determining yields for both green and kiln-dried lumber subjected to different dry kiln schedules. Volume and grade recovery from these small-diameter logs were lower than prior studies suggested. The value of recovered lumber per ft3 of log volume was not found to be affected by log small-end diameter class for black cherry and red oak, but the value was significantly affected for sugar maple. The loss in lumber value that was attributed to kiln-dried based grade changes was greatest for red oak and least for sugar maple. For red oak, the modified dry kiln schedule did not affect the lumber value. For black cherry and sugar maple, there were kiln-schedule based differences in the value of the dry lumber recovered.